Cadaveric Temporal Bone Dissection Workshop in a Tertiary ENT- HNS Centre: Is Our Teaching Satisfactory? - Rayamajhi, Pabina; Shrestha, Susmita; Pradhananga, Rabindra B; Bhattarai, Hari (Medical Journal of Shree Birendra Hospital, 2020)
Introduction: Teaching learning skills are developed through various skill lab procedures. In the Department of ENT and HNS, Temporal Bone Dissection (TBD) is one of the methods of teaching. The TBD workshop conducted in the Department caters to most of the postgraduate students in the country. This study was conducted in the Department of ENT and HNS to evaluate the participants’ satisfaction on TBD course conducted in the Department.Methods: The TBD participants who had undergone TBD course in the Department of ENT and HNS were asked to fill up the questionnaire regarding the satisfaction of the TBD course and suggestions for the improvement of the course. The participants provided the response of the questionnaire in the email or in hand filling of the forms.Results: Total of 42 students responded to the questionnaire regarding the TBD course. 88% of the students graded it as good, 11% replied as satisfactory and 1% of them graded it as needs improvement. Maximum number of students commented on the inadequate time for dissection. Few participants replied the need of live demonstration in the course. 9.5% of the participants who had come for the course more than once commented on the great help done by the course in performing live otology surgery.Conclusions: Maximum participants were satisfied about the TBD workshop which helped them to know the intricate temporal bone anatomy.Key words: otology; questionnaire; Temporal Bone Dissection (TBD)